Highly sensitive square wave voltammetric method for determination of brucine in artificial urine samples based on choline chloride modified glassy carbon electrode. Issue 3 (March 2023) - Biya, Semira; Negash, Negussie; Hailu, Tesfu; Tesfaye, Gizaw; Yaya, Estifanose Ele
Abstract: This paper demonstrates a highly sensitive Voltammetric sensor for determination of brucine (BRU) in artificial urine sample based on choline chloride modified glassy carbon electrode (ChCl/GCE). The simple and cost effective modification was performed by electrodeposition of choline chloride on glassy carbon electrode surface using cyclic voltammetry technique. The modified electrode surface was characterized by electrochemical, spectroscopic and microscopic imaging. The electrode yields a well-resolved peak current for the irreversible oxidation of brucine in the first scan and a pair of quasi-reversible peaks during the second scan. The CV study indicates that brucine undergoes an adsorption controlled electrochemical process with equal number of electrons and protons transfer on the ChCl/GCE. The SWV result shows that the reduction peak current of BRU at the ChCl/GCE was linear in the range of 0.001 μM–10 μM with limit of detection 8 × 10 −5  μM, limit of quantification 2.6 × 10 −4  μM and sensitivity of 116.4 μA/μM. The ChCl/GCE also showed an excellent selectivity, reproducibility and long-time stability towards the electrochemical reduction of Brucine. Moreover, the practical applicability of the fabricated ChCl/GCE was examined in order to determine BRU in artificial urine samples with recovery ranging from 95.5 to 102.7%. The validity of the developed method was confirmed by chromatographic techniques, high-performance liquid chromatography (HPLC) and the results obtained are consistent the HPLC method.